Equilibrium in two-sided markets for payments: Consumer awareness and the welfare cost of the interchange fee - Kim P. Huynh; Gradon Nicholls; Oleksandr Shcherbakov (Bank of Canada, 2022)
The market for payments is an important two-sided one, where consumers benefit from increased merchant acceptance of payment cards and vice versa. The dependence between the decisions that are made on each side of the market results in various network externalities that are often discussed but rarely quantified. We construct and estimate a structural two-stage model of equilibrium in a market for payments in order to quantify the network externalities and identify the main determinants of consumer and merchant decisions. The estimation results suggest significant heterogeneity in consumer adoption costs and benefits. We discuss the critical characteristics that determine which payment instrument is used at the point of sale. Our counterfactual simulation measures the degree of excessive intermediation by credit card providers.
Keywords: C51; D12; E42; L14; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods; Financial services